Shexiang Baoxin Pills Could Alleviate Isoproterenol-Induced Heart Failure Probably through its Inhibition of CaV1.2 Calcium Channel Currents - Jianwei Wu; Juan Yu; Jianyong Qi; Minzhou Zhang (Biochemistry Research International)
Heart failure (HF) affects millions of patients in the world. Shexiang Baoxin Pills (SXB) are extensively applied to treat coronary artery diseases and HF in Chinese hospitals. However, there are still no explanations for why SXB protects against HF. To assess the protective role, we created the HF model in rats by isoproterenol (ISO) subcutaneous injection, 85 milligrams per kilogram body weight for seven days. Four groups were implemented: CON (control), ISO (HF disease group), CAP (captopril, positive drug treatment), and SXB groups. Echocardiography was used to evaluate rats’ HF in vivo. The human CaV1.2 (hCaV1.2) channel currents were detected in tsA-201 cells by patch clamp technique. Five different concentrations of SXB (5, 10, 30, 50, and 100 mg/L) were chosen in this study. The results showed that SXB increased cardiac systolic function and inhibited rats’ cardiac hypertrophy and myocardial fibrosis induced by ISO. Subsequently, it was found that SXB was inhibited by the peak amplitudes of hCaV1.2 channel current (P<0.01). The SXB half inhibitory dosage was 9.09 mg/L. The steady-state activation curve was 22.8 mV depolarization shifted; while the inactivation curve and the recovery from inactivation were not affected significantly. In conclusion, these results indicated that SXB inhibited ISO-induced HF in rats and inhibited the hCaV1.2 channel current. The present study paved the way for SXB to protect itself from HF.